2012
DOI: 10.1007/s00420-012-0758-4
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reports of knee-straining activities at work: a field study with 6-month follow-up

Abstract: ObjectivesTo measure short-term and long-term validity of self-reported duration of kneeling and squatting at work and to examine the possibility of differential misclassification due to knee complaints.MethodsWork-related kneeling and squatting were analysed for 190 male subjects (mean age, 35.0 and SD, 11.5) in field by both measurements and questionnaires. Posture capturing was performed with an ambulatory measuring system (CUELA). Immediately after the measurement (t0), each participant was asked to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…But irrespective of the strategy selected, valid exposure data are still required. A parallel conducted comparison of our measuring data and workers’ self-reports (Ditchen et al 2013) showed that subjects were not able to assess their time spent in knee-straining postures reliably, both immediately after the measurement and six months later. But on the other hand, workers were able to accurately remember the occurrence of different knee-straining postures while performing a specific task.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…But irrespective of the strategy selected, valid exposure data are still required. A parallel conducted comparison of our measuring data and workers’ self-reports (Ditchen et al 2013) showed that subjects were not able to assess their time spent in knee-straining postures reliably, both immediately after the measurement and six months later. But on the other hand, workers were able to accurately remember the occurrence of different knee-straining postures while performing a specific task.…”
Section: Discussionmentioning
confidence: 82%
“…The results show that 75 % of occupational exposure to the knee was in the posture of kneeling and less than 25 % in sitting on heels, squatting, and crawling. This might be an important hint for the interpretation of self-reported exposure to the knee where subjects often fail to assess the duration they spent in different knee postures correctly (Ditchen et al 2013). Despite this predominance of one posture, our findings illustrate huge variety of occupational exposure to the knee and the difficulty of quantifying this exposure by specific categories, for example job categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruusgaard et al (2012) [276] Norway Application of the NMQ in a population group. Ditchen et al (2013) [277] Germany Application of the NMQ in a varied occupational group. Nordander et al (2013) [278] Sweden Application of the NMQ in a varied occupational group.…”
Section: Authors Location Observationsmentioning
confidence: 99%
“…Ditchen et al [277] focused on the time that workers (190 males) were kneeling during their workday and their subsequent knee problems. Nordander et al [278] analysed the risk factors and musculoskeletal disorders of the elbow and hand of a large sample of workers.…”
Section: Varied Occupational Groupsmentioning
confidence: 99%